2021
DOI: 10.1186/s12891-021-04767-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior knee laxity, stiffness, genu recurvatum, and general joint laxity in the late follicular phase and the ovulatory phase of the menstrual cycle

Abstract: Background One risk factor for anterior cruciate ligament (ACL) injury may be fluctuations in female hormones. This study examined variability in joint laxity, as a risk factor for ACL injury, during the menstrual cycle. Methods Subjects were 15 female university students with regular menstrual cycles. We measured estradiol (E2) concentration, anterior knee laxity (AKL), stiffness, genu recurvatum (GR), and general joint laxity (GJL) during the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
(52 reference statements)
1
15
1
Order By: Relevance
“…GJL did not change during the menstrual cycle in either female non-athletes or female athletes, and no difference was apparent between eumenorrhea and oligomenorrhea groups. The results of this study differed from those of previous studies, which showed that GJL changed during the menstrual cycle [ 12 , 18 ]. GJL can be congenital, occurring as a part of connective tissue diseases such as Marfan’s syndrome, Ehlers-Danlos syndrome, and benign joint hypermobility syndrome [ 37 ], or acquired, resulting from stretching of the capsular ligament due to repetitive microtrauma or repetitive use during sports activities [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…GJL did not change during the menstrual cycle in either female non-athletes or female athletes, and no difference was apparent between eumenorrhea and oligomenorrhea groups. The results of this study differed from those of previous studies, which showed that GJL changed during the menstrual cycle [ 12 , 18 ]. GJL can be congenital, occurring as a part of connective tissue diseases such as Marfan’s syndrome, Ehlers-Danlos syndrome, and benign joint hypermobility syndrome [ 37 ], or acquired, resulting from stretching of the capsular ligament due to repetitive microtrauma or repetitive use during sports activities [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…GR in female athletes was significantly higher in the late follicular, ovulation, and luteal phases than in the early follicular phase, although no difference was evident between eumenorrhea and oligomenorrhea groups. These results support previous findings that GR changes during the menstrual cycle [ 12 , 18 ]. Estradiol receptors are present in the human ACL [ 32 ], myofibers of skeletal muscle and capillary endothelial cells [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A questionnaire was administered to 88 female university students. Inclusion criteria were as follows: 1) menstruation approximately 10 times/year, with a menstrual cycle of 25-38 days [14]; 2) no membership in a designated strength club or athletic club and no current history of exercise more than twice a week [15]; 3) no use of oral contraceptives or other hormonal agents within the past 6 months [16]; and 4) no history of doctor-diagnosed disorders or surgery on the lower-limb. Fifteen subjects (mean age, 20 ± 0.5 years; height, 159.2 ± 7.1 cm; weight, 55.9 ± 7.5 kg) who met inclusion criteria 1-4 and consented to participate in the study were included (Fig.…”
Section: Subjectsmentioning
confidence: 99%
“…E2 concentrations were measured from saliva. Because of the possibility of influences on E2 concentration, subjects were asked to strictly observe the following six points before saliva collection, based on previous studies [15,16]: 1) no alcohol consumption for 12 h prior to measurement; 2) no food consumption for 60 min; 3) no brushing the teeth for 45 min; 4) no consumption of dairy products for 20 min; 5) no beverages with high sugar or acid content or caffeine before saliva collection; and 6) in case of dental treatment, no saliva collection within 48 h after the treatment. Subjects were asked to rinse their mouth before starting the experiment, so that no food particles remained in the mouth.…”
Section: Estradiol Concentrationmentioning
confidence: 99%